Adaptation to coastal soils through pleiotropic boosting of ion and stress hormone concentrations in wild Arabidopsis thaliana. Issue 1 (19th July 2021) - Busoms, Silvia; Terés, Joana; Yant, Levi; Poschenrieder, Charlotte; Salt, David E.
Summary: Local adaptation in coastal areas is driven chiefly by tolerance to salinity stress. To survive high salinity, plants have evolved mechanisms to specifically tolerate sodium. However, the pathways that mediate adaptive changes in these conditions reach well beyond Na + . Here we perform a high‐resolution genetic,  ionomic, and functional study of the natural variation in  Molybdenum transporter 1 ( MOT1 ) associated with coastal  Arabidopsis thaliana  accessions. We quantify the fitness benefits of a specific deletion‐harbouring allele ( MOT1 DEL ) present in coastal habitats that is associated with lower transcript expression and molybdenum accumulation. Analysis of the leaf ionome revealed that  MOT1 DEL  plants accumulate more copper (Cu) and less sodium (Na + ) than plants with the noncoastal  MOT1  allele, revealing a complex interdependence in homeostasis of these three elements. Our results indicate that under salinity stress, reduced  MOT1  function limits leaf Na +  accumulation through abscisic acid (ABA) signalling. Enhanced ABA biosynthesis requires Cu. This demand is met in Cu deficient coastal soils through  MOT1 DEL  increasing the expression of SPL7 and the copper transport protein  COPT6 . MOT1 DEL  is able to deliver a pleiotropic suite of phenotypes that enhance salinity tolerance in coastal soils deficient in Cu. This is achieved by inducing ABA biosynthesis and promoting reduced uptake or better compartmentalization of Na +, leading to coastal adaptation.